Case report: Exploring efficacy of tofacitinib in modulating interferon response in five case of anti-MDA5+ dermatomyositis with interstitial lung disease - Zhao, Jie; Bao, Yan; Gao, Ying; Xie, Keliang (Frontiers in Immunology, 2025)
A case report highlights the challenges faced in managing a 66-year-old Chinese woman diagnosed with anti-MDA5 antibody-positive dermatomyositis (MDA5-DM) complicated by rapidly progressive interstitial lung disease (RP-ILD). Despite aggressive therapeutic interventions, her condition rapidly deteriorated, emphasizing the severity and devastating nature of this subtype of DM. A salient feature of her clinical presentation was the marked elevation of interferon (IFN)-γ and IFN-α levels, underscoring the pivotal role that IFNs play in driving the pathogenesis and progression of MDA5-DM-related RP-ILD. In an attempt to stem the relentless progression, tofacitinib, a Janus kinase (JAK) inhibitor, was applied into her treatment regimen. This therapeutic intervention led to a transient decrease in IFN-related cytokines, offering a glimpse of hope that JAK inhibition could modulate the exaggerated IFN response implicated in the disease. Other four similar cases underscore the critical importance of early and aggressive intervention in MDA5-DM patients, as well as the potential therapeutic avenues involving IFN blockers by JAK inhibitors. Urgent and well-designed clinical trials are imperative to unravel the intricate interplay between RP-ILD and the IFN signature in MDA5-DM, and to evaluate novel therapeutic targets that promise long-term efficacy and safety.